Immediate stress dissipation in dual cross-link hydrogels controls osteogenic commitment of mesenchymal stem cells. (15th February 2023) - Pizzolitto, Chiara; Scognamiglio, Francesca; Sacco, Pasquale; Lipari, Sara; Romano, Maurizio; Donati, Ivan; Marsich, Eleonora
Abstract: In vitro studies of mesenchymal stem cells (MSCs) differentiation have been predominantly performed with non-physiologically elastic materials. Here we report the effect of different viscoplastic ECM mimics on the osteogenic engagement of MSCs in 2D. We have developed soft hydrogels, composed of a lactose-modified chitosan, using a combination of permanent and temporary cross-links. The presence of temporary cross-links has a minor effect on the shear modulus of the hydrogels, but causes an immediate relaxation (dissipation) of the applied stress. This material property leads to early osteogenic commitment of MSCs, as evidenced by gene expression of runt-related transcription factor 2 (RUNX2), type 1 collagen (COL1A1), osteocalcin (OCN), alkaline phosphatase enzyme activity (ALP) and calcium deposit formation. In contrast, cells cultured on purely elastic hydrogels with only permanent cross-link begin to differentiate only after a longer period of time, indicating a dissipation-mediated mechano-sensing in the osteogenic commitment of MSCs. Graphical abstract: Unlabelled Image